Acceptance of Mental Health Off Day in Malaysian Job Culture - Yeoh, Wee Win (Journal of Social Sciences and Management Studies, 2023)
The work life balance in Malaysian working culture had been showing concerning signs where the lack of the health working culture had triggered the impact on the mental state of the Malaysian employees. In the same direction, the initiative of the mental health off day had been introduced to promote better wellbeing practice within the employees. However, the employers in Malaysia are still having lack of the action into the initiative of the metal health off days due to multiple concerns. Based on the key findings, there is major highlights on the concerns for the employers towards the understanding on the mental health off day initiative which include the productivity impact, financial impact as well as the shift in the expectations for the employees. However, the employees had viewed the mental health off day as strong positive initiatives that could become a game changer for the working culture in Malaysia. It is believed that the mental health off day will become the big step for the Malaysian working culture to move into the positive direction to promote better mental health among the employees. Therefore, the recommendation had been clear where the mental health off day should be supported by employers and employees to provide the positive impact towards the development of the motivation and retention of the employees.